2006
DOI: 10.1111/j.1540-8159.2006.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety Status of Patients with Implantable Cardioverter Defibrillator and Precipitating Factors

Abstract: Our study indicates presence of depression and anxiety in nearly half of the patients with ICD. Consultation with psychiatry should be a part of the treatment for patients with ICD, especially for those who constitute high-risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
126
4
13

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 47 publications
9
126
4
13
Order By: Relevance
“…Female gender is considered to be an independent risk factor for development of anxiety after implantation of an ICD [39] . It has been found that women do have an increased risk of developing anxiety and depression [19,40] , but the opposite result has also been reported [41] , and in another study only the development of anxiety was related to female gender [42] . More research is needed to explore the meaning of gender in relation to the development of anxiety and depression after implantation of an ICD.…”
Section: Differences In the Primary Emotions In Patients After Icd Immentioning
confidence: 78%
See 3 more Smart Citations
“…Female gender is considered to be an independent risk factor for development of anxiety after implantation of an ICD [39] . It has been found that women do have an increased risk of developing anxiety and depression [19,40] , but the opposite result has also been reported [41] , and in another study only the development of anxiety was related to female gender [42] . More research is needed to explore the meaning of gender in relation to the development of anxiety and depression after implantation of an ICD.…”
Section: Differences In the Primary Emotions In Patients After Icd Immentioning
confidence: 78%
“…An increased level of concern or sadness just before and after implantation of an ICD has earlier been reported [19] .…”
Section: The Intensity Of the Primary Emotionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Concomitant conditions that would shorten life such as cancer deserve a careful evaluation before ICD implantation. Finally, the psychological effect of ICD implantation in young people should be considered because anxiety, depression, and fears are found in nearly half of the patients with ICD (47). Psychiatric consultation should be a part of the treatment for these patients before implantation and during the follow-up (48,49).…”
Section: Identification Of Best Candidates For Icd Implantationmentioning
confidence: 99%